Génies, êtes-vous là ? Consultant, implique-toi ! Devineresse, sois perspicace ! - Camille Van Deputte (Ateliers d'Anthropologie)
For the diviner, divination is “work” (faliwi) that is necessary to satisfy the spirits—and thus maintain balance in one’s personal life—but also a way to help others. It cannot be reduced to a specific communication technique involving invisible entities. What happens during seances is more complex. Diviner, client and spirits all make contributions to developing those intelligible and effective words that constitute the divinatory diagnosis. Their active participation and their adherence can never be taken for granted: do spirits always play their role? Does the client manage to involve themself correctly? Does the diviner succeed in overcoming doubts? The description of a divination seance will make it possible to bring out the words, gestures and material framework on which this particular divinatory pragmatics is based.